A consistency test of fuzzy analytic hierarchy process / Liana Najib and Lazim Abdullah - Najib, Liana; Abdullah, Lazim (2021)
One of the most important steps in Fuzzy Analytic Hierarchy Process (FAHP) is to perform the consistency test of matrix judgment. This test aims at investigating the consistency in decision makers' judgment. It helps to minimize improper decisions made. Nevertheless, this step is more than often opted out by many researchers due to its complexity. This paper, thus intends to introduce a consistency test for matrix judgment in FAHP method. This proposal is obtained by aggregating the decision makers' triangular fuzzy number (TFN), forming a matrix judgment and finalising with matrix determinant. Twenty four different TFN were tested to illustrate the proposed method. Results show that seventeen TFN passed the consistency test, whereas the remaining seven failed. The consistency test offers a significant contribution to check the suitability of TFN in judgement matrix of FAHP.